Perlindungan Direksi Melalui Business Judgment Rule - Dhaifina Fitriani (IAIN Langsa, 2020)
Abstract: The Board of Directors and Business Judgment Rule (BJR) have closed links, especially in the transactions that will be carried out. In carrying out their duties, directors confuse in making decisions. On the one side, a director is required to seek profits from his company, while on the other side when making a wrong decision is considered detrimental to the country's finances and threatened with UU Nomor 20 Tahun 2001 is concerning Corruption Crimes (Corruption). This paper uses analysis studies (analysis studies) by collecting primary data and secondary data from library research (library research) and using a juridical normative approach in analyzing data. Based on these problems it can be concluded that this case is a business economic transaction carried out by a company director based on his own decision. Despite causing harm to the company. The Directors in leading PT Persero are protected by their actions by law through the principle of Business Judgment Rule (BJR) in business economic transactions.